(untitled) (Zaporizhzhia Historical Review, 2021)
Author characterizes regional features of South Ukraine under power of Directory. It’s put characteristics of right-bank part and left-bank part of South. Author proved that events in South Ukraine were proceeded according all-Ukrainian tendencies. It’s established the residential population gave support the Directory.